Toward rational investment decisions: A psychological intervention for Generation Z stock investors - Dava R. Indrawan; Sienly Veronica (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2025)
Investors in Indonesia are often influenced by various financial behaviors affecting investment activities in the capital market. Several indicators lead to irrational investment decision-making such as herding, overconfidence, regret aversion, and representativeness bias. Therefore, this research aimed to determine the impact of herding, overconfidence, regret aversion, and representativeness bias on investment decisions of investors. During the analysis, an analysis was conducted using PLS-SEM with a sample of 271 investors. Data analysis results showed that investment decisions was influenced by herding and overconfidence bias. Meanwhile, regret aversion and representativeness bias did not influence investment decisions of Generation Z investors in Bandung City. This research offered proposals for Generation Z investors in Bandung City to make rational investment decisions by exploring financial science.